Skin lamellar bodies: a unique set of lysosome-related organelles - Mahanty, Sarmistha (Frontiers in Cell and Developmental Biology, 2025)
Skin lamellar bodies (LBs) are crucial for forming and renewing the protective skin barrier, which regulates the body’s internal environment and integrity. LB dysfunction is associated with severe disease conditions such as atopic dermatitis, Netherton syndrome and Harlequin ichthyosis, among others. Despite its importance in human physiology, the intracellular origin and biogenesis mechanism of LBs remain largely unknown. LBs are lysosome-related organelles (LRO), a group of cell type-specific organelles having unique structures, cargo content, and function. Classical LROs such as melanosomes, lung lamellar bodies and Weibel-Palade bodies share overlapped molecular machinery/mechanisms and are co-affected in genetic disorders like Hermansky-Pudlak syndrome (HPS) or Chédiak-Higashi syndrome (CHS). In contrast, LBs contain a diverse array of protein and lipid cargo that are notably different from those found in other LROs, and LBs are not reported to be affected in HPS/CHS. LBs form in an advanced differentiation state of keratinocytes while cells are experiencing high ions and low nutrients in their exterior, the plasma membrane (PM) undergoing modifications, and intracellular organelles starting to disappear. This article discusses atypical conditions of LB biogenesis in comparison to classical LROs, which may potentially guide future research on LB biogenesis.